Penugasan Dosen di Sekolah Dalam Upaya Meningkatkan Kualitas Pembelajaran IPA di Sekolah Menengah - Lina Agustina; Putri Agustina; Rina Astuti; Annur Indra Kusumadani (Semar: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Lecturer Assignment Program in Schools  is a government effort to provide real-world experience to LPTK lecturers in teaching practices in schools. Lecturers are expected to have relevant experience so they can serve as professional role models for prospective teacher students. This activity aims to provide lecturers with direct experience in implementing teaching in secondary schools while supporting the improvement of learning quality. The activity was carried out at SMP IT Amanah Juwiring through three stages: Focus Group Discussions (FGD) with the school, implementation of learning using teaching modules and LKPD based on Problem Based Learning (PBL), and evaluation through observation, interviews, and reflection with teachers. The results of the activity showed an increase in student activeness in discussions and questions and answers, more participatory learning, and increased teacher awareness in the use of media and various learning models. This program not only impacts students, but also strengthens professional collaboration and teacher competency development in designing more innovative and student-centered learning.